A new fractional model applied to description of the viscoelastic creep behavior of two Brazilian oils and their w/o emulsions - Wesley P. do Carmo; Alexandre F. Santos; Marcelo Kaminski Lenzi; Montserrat Fortuny; Ervin K. Lenzi (Digital Chemical Engineering, 2023)
The objective of this work was to investigate and model the viscoelastic creep behavior of two Brazilian crude oils: A (API 16.8) and B (API 24.6), with different contents of aromatics, resins and asphaltenes and their W/O emulsions with water contents between 0 to 55%. Stable emulsions were prepared using an Ultra-Turrax homogenizer and the viscoelastic flow data were obtained from an Anton Paar controlled voltage Rheometer with plate-plate geometry. For modeling purposes, the fractional model was able to describe the experimental data very well obtaining a mean correlation coefficient (R¯2)equal to 0.9956 and root mean squared errors (RMSE) of the order of 10−13 for oil A and its emulsions and 10−12 for oil B and its emulsions.